The impact of changes in the employment structure on convergence of human capital in Poland and Europe - Kusideł, Ewa; Gajdos, Artur (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The main purpose of this paper is the analysis of internal and external convergence processes and to present changes in working force structure in cross-section level of education and major occupational groups in Poland on regional level and in the European Union countries. Spatial differentiation of human capital quality is the main element of education policy. Also, the assessment of the transformation process to knowledge-based economy requires spatial as well as multi cross-section data analysis. The study attempts to in-depth analysis of the problem, assuming that beyond the level of education a significant differentiating of human capital quality in the spatial and cross-section level can be a course of education (occupation). Data which concern labour force structure in level of education and major occupational groups taken from Labour Force Survey have been used in this paper. The data source specificity enables the assessment of labour force professional specialization and the changes of this specialization with time. Combined analysis of spatial and structural changes with the method of time-series-cross-section data analysis makes it possible to draw conclusions about processes occurring on national and regional labour markets. In-depth analysis of the labor market occupational structure in the spatial cross-section is an important theoretical and practical area of study necessary for an effective labor market policies and education system.